(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
This article explores the role and significance of artificial intelligence (AI) technologies in biology education. It analyzes how AI tools can enhance the effectiveness and interactivity of the learning process. Using examples such as ChatGPT, Google Bard, BioDigital Human, Labster, and others, the paper discusses the applications, advantages, and limitations of these platforms in teaching biology. Recommendations for integrating AI technologies into the educational system are also provided.